Towards Intelligently - Sustainable Cities? - Salvati, Luca; Gargiulo Morelli, Vittorio; Weijnen, Margot; van Bueren, Ellen; Wenzler, Ivo; De Reuver, Marke (TeMA - Journal of Land Use, Mobility and Environment, 2013)
In the quest for achieving sustainable cities, Intelligent and Knowledge City Programmes (ICPs and KCPs) represent<span style="line-height: 200%; font-family: "Century Gothic","sans-serif"; font-size: 10pt; mso-bidi-font-size: 11.0pt; mso-ansi-language: EN-GB; mso-bidi-font-family: Calibri; mso-bidi-theme-font: minor-latin;" lang="EN-GB"> cost-efficient strategies for improving the overall performance of urban systems. However, even though nobody argues on the desirability of making cities “smarter”, the fundamental questions of how and to what extent can ICPs and KCPs contribute to the achievement of urban sustainability lack a precise answer. In the attempt of providing a structured answer to these interrogatives, this paper presents <span style="line-height: 200%; font-family: "Century Gothic","sans-serif"; font-size: 10pt; mso-bidi-font-size: 11.0pt; mso-ansi-language: EN-US; mso-bidi-font-family: Calibri; mso-bidi-theme-font: minor-latin;" lang="EN-US">a methodology developed for investigating the modalities through which ICPs and KCPs contribute to the achievement or urban sustainability. Results suggest that ICPs and KCPs efficacy lies in supporting cities achieve a sustainable urban metabolism through optimization, innovation and behavior changes.